Digestibilidade Verdadeira da Lisina HCl e da Lisina Sulfato Determinada com Galos Cecectomizados - Neme, Rafael [UNESP]; Albino, Luiz Fernando Teixeira; Rostagno, Horacio Santiago; Rodrigueiro, Ramalho José Barbosa; Nunes, Ricardo Vianna (My University, 2001)
The objective of this experiment was to determine the true digestibility of lysine HCl and lysine sulfate, with ceccctomized adult roosters. Eighteen roosters, 2.854 kg live weight, were cecectomized and kept in cages for a period of 10 days. After two days of adaptation to the cages the animals were fed twice a day during one hour (8:00 a.m. to 9:00 am and 4:00 p.m. to 5:00 pm), for crop dilation to avoid regurgitation of the feed. The forced fed method was utilized, with 12 roosters placed in individual cages equipped with excreta collection pans. The experiment design was complete randomized, with two treatments (two lysine sources) each one with six replicates. Also six birds were fasted to determine the endogenous/metabolic loses. Diets and excreta were analyzed to determine amino acid contents and the true lysine digestibility coefficients calculatted. The true digestibility coefficients, in percentage, were 97.59% for lysine HCl and 98.34% for lysine sulfate, they were not statistically different.
True Digestibility of Lysine HCl and Lysine Sulfate Determinated with Cecectomized Adult Roosters
Keywords: Cecectomized roosters; Forced fed; Lysine; True digestibility